A simplified method for blood feeding, oral infection, and saliva collection of the dengue vector mosquitoes - Sri-in, Chalida; Weng, Shih-Che; Shiao, Shin-Hong; Tu, Wu-Chun (PloS one, 2020)
A simple device using folded Parafilm-M as an artificial blood feeder was designed for studying two important dengue vector mosquitoes, Aedes aegypti and Aedes albopictus. The efficiency of the artificial blood feeder was investigated by comparing the numbers of engorged mosquitoes that fed on the artificial blood feeder versus mice as a live blood source. Significantly more engorged females Aedes aegypti fed on the artificial blood feeder than on mice. In addition, the artificial feeder could serve as a useful apparatus for oral infection via artificial blood meals, and for saliva collection in mosquitoes. Our method enabled us to collect saliva from multiple mosquitoes at once, providing sufficient infected saliva for determination of the virus titer by plaque assay analysis. Our artificial feeder has the advantage that it is simple, inexpensive, and efficient.